Flexible Working Arrangements (FWAs) in Malaysia: Are We There Yet? - Sharija Che Shaari; Sharifah Rahama binti Amirul (2020)
The nature of work has changed and evolved to be in tandem with the societies' advancement. Many business organisations, especially in the developed countries, have taken up the work-life balance (WLB) which can be realised through flexible working arrangements (FWAs) as they could see the benefits of FWAs upon the sustainability of their businesses and the well-being of their employees. FWAs refer to arrangements that allow employees some degree of flexibility and control over when, where, and how their work is performed. FWAs are not something new, especially in developed countries such as the United Kingdom, the United States, Australia and Germany. FWAs offer a wealth of benefits such as improve the well-being of employees by promoting work-life balance, maintaining talent pool through effective recruitment and retention; and one of the mechanisms to boost the employees' productivity. Thus, it is the objective of this study to explore whether the existing Malaysian employment law is sufficient to deal with FWAs. In achieving its aim, this study uses a doctrinal legal research methodology. It is an established traditional genre of research in the legal field which is concerned with the systematic analysis of the legal doctrine, legal rules, principles, concepts, theories and principle of all types of case, statutes and rules or a combination of some or all of them. It is interesting to note there are three main statutes in Malaysia which protect the minimum rights of employees. This legislation is segregated based on three different regions in Malaysia. First is the Malaysia Employment Act 1955 (Act 265) covers employees in Peninsular Malaysia. Next are the Sabah Labour Ordinance 1950 (Cap 67) and Sarawak Labour Ordinance 1959 (Cap 76) which cover employees in the states of Sabah and Sarawak respectively. It is submitted here that existing Malaysia's employment law is inadequate to deal with FWAs. The finding will be useful in adding to the existing literature. It will also benefit the policymakers should they intend to formulate specific legislation governing FWAs. In conclusion, it is pertinent for Malaysia to have specific legislation dealing with FWAs in place.